The ficolin response to LPS challenge in mice. (April 2019) - Jarlhelt, Ida; Genster, Ninette; Kirketerp-Møller, Nikolaj; Skjoedt, Mikkel-Ole; Garred, Peter
Highlights: LPS-induced inflammation can induce a significant ficolin response in mice. Murine ficolin mRNA- and protein levels is induced upon LPS challenge, exhibiting acute phase behavior. Ficolin expression and protein secretion seem to be regulated by a negative feedback mechanism. Two novel sandwich ELISAs was established based on rat monoclonal antibodies against murine ficolins. Abstract: The ficolins belong to an important family of pattern recognition molecules, which contributes to complement activation via the lectin pathway. How the ficolins respond to inflammatory stimuli remains only partly understood. In the present study, we investigated the ficolin A and ficolin B expression and protein distribution patterns in a mouse model of LPS-induced inflammation. The time- and tissue-specific expression of ficolin A and B was determined by real time PCR. Furthermore, ficolin protein levels in serum and bone marrow extracts from LPS challenged mice were determined by novel in-house developed sandwich ELISAs. Ficolin A was mainly expressed in liver and spleen. However, our data also suggested that ficolin A is expressed in bone marrow, which is the main site of ficolin B expression. The level of ficolin A and B expression was increased after stimulation with LPS in the investigated tissues. This was followed by a downregulation of expression, causing mRNA levels to return to baseline 24 h post LPS challenge. Protein levels appeared to follow the same pattern as the expression profiles, with an exception of ficolin B levels in serum, which kept increasing for 24 h. Ficolin A was likewise significantly increased in bronchoalveolar lavage fluid from mice infected with the fungi A. fumigatus, pointing towards a similar effect of the ficolins in non-sterile mouse models of inflammation. The results demonstrate that LPS-induced inflammation can induce a significant ficolin response, suggesting that the murine ficolins are acute phase reactants with increase in both mRNA expression and protein levels during systemic inflammation.